2007
DOI: 10.1105/tpc.106.047720
|View full text |Cite
|
Sign up to set email alerts
|

TheArabidopsis irregular xylem8Mutant Is Deficient in Glucuronoxylan and Homogalacturonan, Which Are Essential for Secondary Cell Wall Integrity

Abstract: The secondary cell wall in higher plants consists mainly of cellulose, lignin, and xylan and is the major component of biomass in many species. The Arabidopsis thaliana irregular xylem8 (irx8) mutant is dwarfed and has a significant reduction in secondary cell wall thickness. IRX8 belongs to a subgroup of glycosyltransferase family 8 called the GAUT1-related gene family, whose members include GAUT1, a homogalacturonan galacturonosyltransferase, and GAUT12 (IRX8). Here, we use comparative cell wall analyses to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
264
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 261 publications
(286 citation statements)
references
References 48 publications
20
264
2
Order By: Relevance
“…In addition, the double mutant held reduced levels of cellulose and displayed a concomitant increase in uronic acids compared with the single mutants (see Supplemental Figure 5D online). These data suggest that CTL activity is not essential for cellulose production, since complete block of primary wall cellulose synthesis results in collapsed pollen grains (Persson et al, 2007a), which was not observed in the ctl1 ctl2 double mutants.…”
Section: Ctl1 and Its Close Homolog Ctl2 Are Functionally Equivalentmentioning
confidence: 80%
See 1 more Smart Citation
“…In addition, the double mutant held reduced levels of cellulose and displayed a concomitant increase in uronic acids compared with the single mutants (see Supplemental Figure 5D online). These data suggest that CTL activity is not essential for cellulose production, since complete block of primary wall cellulose synthesis results in collapsed pollen grains (Persson et al, 2007a), which was not observed in the ctl1 ctl2 double mutants.…”
Section: Ctl1 and Its Close Homolog Ctl2 Are Functionally Equivalentmentioning
confidence: 80%
“…Due to functional redundancies of the CESA6-related position in the CSC, prc1-1 only displays modest phenotypes (Persson et al, 2007a). If CTL1 generally affects primary wall cellulose deposition, we would therefore expect the ctl1-1 mutant to have an additive phenotype when crossed to prc1-1.…”
Section: Ctl1 Affects Primary Wall Cellulose Depositionmentioning
confidence: 99%
“…The idea of a terminal oligosaccharide playing a role in the regulation of polysaccharide size has been proposed for glucuronoxylan synthesis in Arabidopsis (York and O'Neill, 2008). It was found that a normal chain length of glucuronoxylan requires the presence of a GalA-containing tetrasaccharide sequence that is located at the reducing end of the polysaccharide, and mutation of the GAUT12/IRREGLULAR XYLEM8 (IRX8) gene results in lower levels of xylan synthesis and altered polymer length (Peña et al, 2007;Persson et al, 2007). If such a primer/terminator exists on RG-I, it would only account for a small percentage of the total mass of the mucilage, and its absence or alteration would be difficult to detect by any of the methods applied in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our observations, down-regulation of noncellulosic polysaccharide biosynthesis using RNA interference approaches would be predicted to result in changes to both lignification and microfibril orientation, offering many opportunities for studying cell wall assembly. In Arabidopsis (Arabidopsis thaliana), a number of mutants have been identified that have altered xylan biosynthesis with reduced amount and altered structure expressed in xylem and interfascicular fibers (fra8, irx8, irx9, and PARVUS; Zhong et al, 2005;Persson et al, 2007;Lee et al, 2007aLee et al, , 2007b. The main phenotypes observed are a reduction in fiber wall thickness and/or increased stem brittleness.…”
Section: Xylans Are Associated With Reorientation Of Cellulose Microfmentioning
confidence: 99%